Forecast Errors and the Effect of Underwriter Reputation and Auditor Influence During Listing on IPOs - Mahussin, Norlida (2003)
The engagement of reputable underwriter and auditor by the listing firm is believed to provide a positive signal to the market, thus reducing the uncertainty surrounding the firm's value. Since audit quality is differentiated, some of the issuing firms switch to more reputable auditors during listing to increase the credibility of the financial information in the prospectus. The disclosure of earnings forecast in the prospectus is also perceived to provide information that could reduce the uncertainty. However, evidence from previous studies on these issues is inconclusive. This study investigates the effect of underwriter reputation, auditor choice and auditor switch during listing and earning forecast error on the level of IPOs initial returns. Thus, the main objective is to examine whether these factors provide a signal to potential investors in IPOs that might have consequences on the level of initial return. This study also examines the relationship between the engagement of quality differentiated audit firms and level of earning forecast errors.